Prevalence and profile of positive dogs for leishmaniasis in a veterinary hospital of Rio Grande do Sul (2017-2019) - Mariga, Carollina; Dourado Guerra Segundo, Daniel; Melazzo de Andrade, Cinthia; Krause, Alexandre; Tadeu Lemos Pinto Filho, Saulo (Pubvet, 2021)
This study aimed to classify the clinical profile of dogs affected by leishmaniasis at the Veterinary Hospital of Universidade Federal de Santa Maria (HVU-UFSM). The clinical histories of the animals seen at the hospital from January 2017 to July 2019 were reviewed, using the patients’ medical records. During this period, 250 animals were suspected to have leishmaniasis and 61 (24,4%) of the animals tested positive. The clinical profiles were classified according to breed, gender, age, and vaccination status, then further separated according to the clinical signs the presence of concomitant diseases, and bodily systems involved: digestive, neuromuscular, multisystemic, hematopoietic, respiratory, lymphatic, ophthalmic, urinary and cutaneous. This study revealed that leishmaniasis most affects animals of mixed breed, particularly two to five years old males. The disease most often occurs in the cutaneous system, followed by multisystem presentation.
Keywords: Canine; clinical profile; clinical signs; leishmaniosis; systems